Assessing the Functional Relevance of Variants in the IKAROS Family Zinc Finger Protein 1 (IKZF1) in a Cohort of Patients With Primary Immunodeficiency - Eskandarian, Zoya; Fliegauf, Manfred; Bulashevska, Alla; Proietti, Michele; Hague, Rosie; Smulski, Cristian Roberto; Schubert, Desirée; Warnatz, Klaus; Grimbacher, Bodo (Frontiers in Immunology, 2019)
Common variable immunodeficiency (CVID) is the most frequent symptomatic primary immunodeficiency. Patients with CVID are prone to recurrent bacterial infection due to the failure of adequate immunoglobulin production. Monogenetic defects have been identified in approximately 25% of CVID patients. Recently, mutations in IKZF1, encoding the zinc-finger transcription factor IKAROS which is broadly expressed in hematopoietic cells, have been associated with a CVID-like phenotype. Herein we describe eleven patients with heterozygous IKZF1 variants from eight different families with autosomal dominant CVID and two siblings with an IKZF1 variant presenting with inflammatory bowel disease (IBD). This study shows that mutations affecting the DNA binding domain of IKAROS can impair the interaction with the target DNA sequence thereby preventing heterochromatin and pericentromeric localization (HC-PC) of the protein. Our results also indicate an impairment of pericentromeric localization of IKAROS by overexpression of a truncated variant, caused by an immature stop codon in IKZF1. We also describe an additional variant in TNFSF10, encoding Tumor Necrosis Factor Related Apoptosis Inducing Ligand (TRAIL), additionally presented in individuals of Family A. Our results indicate that this variant may impair the TRAIL-induced apoptosis in target cell lines and prohibit the NFᴋB activation by TRAIL and may act as a modifier in family A.